Health Lifestyles across the Transition to Adulthood: Implications for Health - Lawrence, Elizabeth (Soc Sci Med, 2017)
Research has long established the importance of individual health behaviors such as cigarette smoking for adult morbidity and mortality. However, we know little about how health behaviors cluster into health lifestyles among adolescents and young adults in the United States, or in turn, how such health lifestyles are associated with young adult health outcomes. This study establishes health lifestyles as distinct group phenomena at three developmental time points in a single cohort: late adolescence (ages 15–17), early adulthood (ages 20–24), and young adulthood (ages 26–31). We then identify the associations between these health lifestyles and young adult health outcomes. We use the National Longitudinal Study of Adolescent to Adult Health (Add Health), a nationally representative sample of U.S. adolescents followed into adulthood, and latent class analysis and regression models. We uncover diverse health lifestyles among adolescents, early adults, and young adults; however, few individuals engaged in a consistently salubrious lifestyle at any developmental stage. People with less healthy lifestyles also tended to exhibit poorer health in young adulthood. Our results showed that young adult health lifestyles were significantly associated with young adult cardiovascular risk. Moreover, health lifestyles in each of the three developmental stages were associated with young adult self-rated health, and accounting for lifestyles in later stages explained some of these associations. Overall, this study suggests a portrait of problematic health lifestyles among a nationally representative cohort of young Americans, with associated patterns of relatively poor physical health among those with poor health lifestyles.